Sustainable Waste Governance Framework via Web-GIS: Kadikoy Case - Karademir, Melda; Acimert, Buket Aysegul Ozbakir (MDPI, 2024)
Waste management, one of the fundamental problems of today, is at the center of sustainability discussions. The failure to adopt a holistic and participatory approach in traditional waste management highlights the need to develop new approaches. The main purpose of this research is to present the basic components of a Web-GIS-based platform design for sustainable waste governance. The presented framework emphasizes that waste management is not a problem of local or central government and that holistic sustainable waste governance can be achieved with the participation of all relevant stakeholders. The Kadikoy district of Istanbul, a metropolitan city, was selected as the study area. Information was collected from the study area with quantitative and qualitative analysis methods. The results obtained with fieldwork and survey data show that there is a need for a location-based platform that allows relevant stakeholders to see the current waste management workflow, enter data themselves, and provide feedback. The Web-GIS-based platform proposed in this article to meet this need is an important step in ensuring sustainable waste governance. In the article, a Web-GIS-based platform has been developed to ensure the sustainable waste governance of commercial enterprises for local governments.
Keywords: waste governance; sustainability; geographic information systems; sustainable development goals; Kadikoy; QUALITY-OF-LIFE; MANAGEMENT; TECHNOLOGY; INDICATORS; Science & Technology - Other Topics; Environmental Sciences & Ecology